2021
DOI: 10.1038/s41598-021-92307-8
|View full text |Cite
|
Sign up to set email alerts
|

Multi-institutional retrospective analysis of ultrahypofractionated radiotherapy for Japanese prostate cancer patients

Abstract: To report outcomes and risk factors of ultrahypofractionated (UHF) radiotherapy for Japanese prostate cancer patients. This multi-institutional retrospective analysis comprised 259 patients with localized prostate cancer from 6 hospitals. A total dose of 35–36 Gy in 4–5 fractions was prescribed for sequential or alternate-day administration. Biochemical failure was defined according to the Phoenix ASTRO consensus. Toxicities were assessed using National Cancer Institute Common Toxicity Criteria version 4. Tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“… DeRT = dose escalated radiotherapy, UHF = ultrahypofractionated radiotherapy, H-UHF = high-dose UHF (EQD2 > 100 Gy 1.5 ), L-UHF = low-dose UHF (EQD2 ≤ 100 Gy 1.5 ), fr = fractions, EQD2 = n × d ([α/β] + d)/([α/β] + 2) where n = number of treatment fractions, d = dose per fraction in Gy, α/β = 1.5 Gy. Koontz et al reported that EQD2 > 100 Gy 1.5 might cause high rates of >Grade 2 toxicities [ 9 ] and Ishiyama et al confirmed those results [ 4 ]. Therefore, we examined the impact of this threshold not only on toxicity but also on the efficacy of UHF and DeRT, dividing UHF into two subgroups: H-UHF and L-UHF groups, using a cut-off value of EQD2 = 100 Gy 1.5 .…”
Section: Figurementioning
confidence: 83%
See 3 more Smart Citations
“… DeRT = dose escalated radiotherapy, UHF = ultrahypofractionated radiotherapy, H-UHF = high-dose UHF (EQD2 > 100 Gy 1.5 ), L-UHF = low-dose UHF (EQD2 ≤ 100 Gy 1.5 ), fr = fractions, EQD2 = n × d ([α/β] + d)/([α/β] + 2) where n = number of treatment fractions, d = dose per fraction in Gy, α/β = 1.5 Gy. Koontz et al reported that EQD2 > 100 Gy 1.5 might cause high rates of >Grade 2 toxicities [ 9 ] and Ishiyama et al confirmed those results [ 4 ]. Therefore, we examined the impact of this threshold not only on toxicity but also on the efficacy of UHF and DeRT, dividing UHF into two subgroups: H-UHF and L-UHF groups, using a cut-off value of EQD2 = 100 Gy 1.5 .…”
Section: Figurementioning
confidence: 83%
“…The detailed method of radiotherapy (UHF [ 4 , 5 ] or DeRT [ 6 ] in Uji-Takeda Hospital [ 8 ]) has been described elsewhere. All patients were treated with UHF or DeRT at various fractions ( Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several randomized controlled trials indicated the superiority of BT boost over external beam radiotherapy alone 8 10 not only in LDR 8 but also in HDR 9 , 10 , there is a lack of conclusive data comparing BT ± EBRT and UHF 11 15 . Therefore, to compare the results of UHF to BT ± EBRT, we used open data constructed by multi-institution data accumulation in Japan 16 . In addition, as previous studies cited that a BED over 226 Gy 1.5 might be a threshold to cause higher rates of grade > 2 toxicities 16 , 17 in UHF, we divided the UHF group into L-UHF (BED < 226 Gy 1.5 ) and H-UHF (BED ≥ 226 Gy 1.5 ) groups using this threshold.…”
Section: Introductionmentioning
confidence: 99%